Mirror, mirror on the wall, who is transitioning amongst them all? - Isabelle Cathérine Hinsche; Rainer Klump (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
In order to reach climate neutrality by 2050, the European Union is taking action in the form of extensive sustainability regulations with the aim to push the private sector towards sustainable economic activities. In this context, a new instrument to finance a company's sustainability transition has been developed: the sustainability-linked bond (SLB). This paper analyzes the SLB market's efficiency in attracting those companies that are most crucial for a successful sustainability transition, namely carbon-intensive companies and companies that are lagging behind in their sustainability transition, defined as ESG laggards. By developing a conceptual framework for the SLB market and running a probit and logit regression estimation, this paper shows that the SLB market efficiently attracts carbon-intensive companies, but fails to attract ESG laggards. Moreover, the paper identifies four success factors for the SLB market to improve its future accessibility and credibility.
Keywords: C25; G10; G14; G18; G38; Q01; Q58; 330; Sustainable Finance; Sustainability-Linked Bonds; Transition Financing; Sustainable Investing; ESG; Market Efficiency